Supply Chain Management in Moderating the Effect of Intra Group Transaction in Company Development - Agus Bandiyono; Etty Murwaningsari (International Journal of Supply Chain Management, 2020)
Abstract— The research aims to determine the effect of multinationality, thin capitalization and intragroup transactions on tax avoidance in supply chain Management as moderating variables and firm size, profit, and debts as control variables. The data in this study are secondary data from property sector companies listed on the Indonesia Stock Exchange. The results showed that the multinationality variable and intra-group transactions did not significantly influence company development in Supply Chain Management, the thin capitalization variable had a significant effect on tax avoidance in supply chain management, moderation variable affected multi-nationality, negatively the tax avoidance in supply chain management, moderation variable affected Thin capitalization and intragroup transactions positively towards tax avoidance in supply chain management, as moderating variables will be able to strengthen the relationship of multinationality, thin capitalization and intragroup transactions to tax avoidance in supply chain management, firm size, profit, and debts control variables do not have a significant relationship between the level of Tax avoidance in supply chain management with multinationality, variables firm size, profit and debts controls have a significant relationship between the level of company in supply chain management with thin capitalization and intra-group transactions.